Paclitaxel improves outcome from traumatic brain injury - Cross, Donna J. (Brain Res, 2015)
Pharmacologic interventions for traumatic brain injury (TBI) hold promise to improve outcome. The purpose of this study was to determine if the microtubule stabilizing therapeutic paclitaxel used for more than 20 years in chemotherapy would improve outcome after TBI. We assessed neurological outcome in mice that received direct application of paclitaxel to brain injury from controlled cortical impact (CCI). Magnetic resonance imaging was used to assess injury-related morphological changes. Catwalk Gait analysis showed significant improvement in the paclitaxel group on a variety of parameters compared to the saline group. MRI analysis revealed that paclitaxel treatment resulted in significantly reduced edema volume at site-of-injury (11.92 ± 3.0 and 8.86 ± 2.2 mm(3) for saline vs. paclitaxel respectively, as determined by T2-weighted analysis; p ≤ 0.05), and significantly increased myelin tissue preservation (9.45 ± 0.4 vs. 8.95 ± 0.3, p ≤ 0.05). Our findings indicate that paclitaxel treatment resulted in improvement of neurological outcome and MR imaging biomarkers of injury. These results could have a significant impact on therapeutic developments to treat traumatic brain injury.